Avatar, the last airbender. Imbalance. Part three - Hicks, Faith Erin (Dark Horse Books, 2019)
Aang must decide if he should take away Liling's bender abilities after Ru and Yaling free her from imprisonment. Later, Ru and Yaling regret freeing their mother and Aang must try to stop her from destroying the village inhabitants.